Bond strength between corroded steel reinforcement and recycled aggregate concrete. (June 2019) - Alhawat, Musab; Ashour, Ashraf
Abstract: This paper investigates the bond performance of recycled coarse aggregate (RCA) concrete with un-corroded/corroded reinforcing steel bars, with the main parameters being RCA content, corrosion level, bar diameter and embedment length. For this purpose, 60 pull-out specimens containing different percentages of RCA (i.e. 0%, 25%, 50% and 100%) and steel bars of two diameters (12 and 20 mm) and different embedment lengths were tested. In order to establish various levels of corrosion, specimens were exposed to an electrochemical corrosion for 2, 5, 10 and 15 days. The bond strength between RAC concrete and un-corroded/corroded steel are compared to current codes and equations proposed by other researchers. Experimental results showed that larger corrosion rate of steel bars was observed with the increase of the replacement level of RCA due to its high porosity and water absorption. The use of RCA had a slight influence on bond strength for un-corroded specimens compared to that obtained from conventional concrete. Furthermore, the bond strength of RCA concrete was strongly affected by corrosion products; bond strength slightly enhanced for up to about 2% corrosion rate, and then significantly decreased as the corrosion time further increased, similar to that of conventional concrete. However, the rate of bond degradation between RCA concrete and corroded steel bars was much faster than that observed in corroded conventional concrete.